Brucella eradications program: Course and considerations serological and microbiological tests results - Γιαντζής, Δ. Γ. (Journal of the Hellenic Veterinary Medical Society, 2019)
The serological and microbiological tests' results made on serum samples and fetuses of bovine and small ruminants during the years 1977-1981 are reported and discussed. The percentage of positive bovine serums was reduced from 4.70% (1977) to 1.50% (1981). The percentage of small ruminants' positive foetuses was reduced from 49.43% (1976) to 8.16% (1981). The born infected calves to infected dams ranged up to 24.3%. Human cases in Greece are going in decrease: from 1702 (1976) to 948 (1981). This result could be attributed to the reduced sources of infection